2017
DOI: 10.1016/s0140-6736(16)32517-x
|View full text |Cite|
|
Sign up to set email alerts
|

Atezolizumab versus docetaxel in patients with previously treated non-small-cell lung cancer (OAK): a phase 3, open-label, multicentre randomised controlled trial

Abstract: F. Hoffmann-La Roche Ltd, Genentech, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

109
3,648
10
39

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,036 publications
(3,959 citation statements)
references
References 23 publications
109
3,648
10
39
Order By: Relevance
“…Improvements in median OS associated with ICBs versus other therapies have been reported in several cancer types (Table 2), including RCC treated with nivolumab versus the targeted agent everolimus [28], NSCLC treated with either pembrolizumab or atezolizumab versus the chemotherapeutic agent docetaxel [42,57], and UC treated with pembrolizumab versus chemotherapy [46]. However, as novel agents extend patient survival times, it becomes increasingly difficult to conduct long clinical trials in order to measure OS [75,76].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in median OS associated with ICBs versus other therapies have been reported in several cancer types (Table 2), including RCC treated with nivolumab versus the targeted agent everolimus [28], NSCLC treated with either pembrolizumab or atezolizumab versus the chemotherapeutic agent docetaxel [42,57], and UC treated with pembrolizumab versus chemotherapy [46]. However, as novel agents extend patient survival times, it becomes increasingly difficult to conduct long clinical trials in order to measure OS [75,76].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
“…Some studies investigating ICBs in NSCLC, RCC, HNSCC, and UC have demonstrated increased OS in the absence of a PFS benefit [27,28,31,42,47,57], whereas other trials in melanoma and NSCLC have demonstrated increased OS, as well as ORR and PFS, compared with standard of care (Table 2) [23,43].…”
Section: Endpoints To Assess Clinical Outcomes Associated With Icbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of activity of PD-1/PD-L1-directed agents has also been observed in patients who are never smokers and in patients with EGFR mutation-positive NSCLC [51, 52, 61]. It has been shown that NSCLC patients with tumors that have a high mutational burden have a greater probability of benefit from checkpoint inhibition [62].…”
Section: Post-alk Inhibitor Therapymentioning
confidence: 99%
“…Although PD‐1 checkpoint inhibitors, including nivolumab, are now standard treatment for previously treated advanced non‐small cell lung cancer (NSCLC),1, 2, 3 patients with coexisting interstitial lung disease (ILD) were excluded from the original clinical trials for fear of exacerbating this condition 4. Idiopathic pulmonary fibrosis (IPF) is a specific form of ILD characterized by chronic progressive fibrosing interstitial pneumonia of unknown cause and is potentially fatal.…”
Section: Introductionmentioning
confidence: 99%